Kepuasan Kerja Sebagai Mediasi Antara Work Family Conflict Terhadap Kinerja Karyawan Pastry Shop Retawu Deli Malang - Azza, Bilqiis Rihhadatul; Djaelani, Abdul Kodir; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of work family conflict on employee performance with job satisfaction as a mediating variable. The research method used is quantitative with a causal associative approach. Data were collected through distributing questionnaires to all employees of Retawu Deli Malang pastry shop with saturated sampling technique, so that the number of samples used in this study was 51 respondents. Data analysis was performed using the Partial Least Square (PLS) method using SmartPLS 3.0 software. The results of the study showed that work family conflict did not have a significant effect on employee performance or job satisfaction. On the contrary, job satisfaction has a positive and significant effect on employee performance. In addition, job satisfaction cannot act as a mediator in the relationship between work family conflict and employee performance. These findings show that in the context of the service industry such as the Retawu Deli pastry shop, the job satisfaction factor is more dominant in determining employee performance than work-family conflict. Therefore, employee performance improvement strategies should be focused on creating a more flexible and supportive work environment, as well as providing incentives that can increase employee job satisfaction. Keywords: Work family conflict, Service Industry, Mediation, Employee Performance, Job Satisfaction